2012
DOI: 10.3390/molecules17032330
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antimicrobial Activity and Resistance to Oxidation of Moringa peregrina Seed Oil

Abstract: Abstract:The antimicrobial activity of the oil extracted with n-hexane from the seeds of Moringa peregrina was tested against Staphylococcus aureus, S. epidermidis, Pseudomonas aeruginosa, Escherichia coli, Enterobacter cloacae, Klebsiella pneumoniae, Candida albicans, C. tropicalis and C. glabrata. The oil proved effective against all of the tested microorganisms. Standard antibiotics (netilmycin, 5-flucytocine, intraconazole and 7-amino-4-methylcoumarin-3-acetic acid) were used for comparison. The resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 7 publications
(12 reference statements)
3
27
1
1
Order By: Relevance
“…It belongs to the Moringaceae family that has only one genus called Moringa with 13 species (Steinitz et al 2009). The most famous Moringa species are Moringa oleifera and Moringa peregrina (Lalas et al 2012). M. peregrina is distributed in tropical and non-tropical areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It belongs to the Moringaceae family that has only one genus called Moringa with 13 species (Steinitz et al 2009). The most famous Moringa species are Moringa oleifera and Moringa peregrina (Lalas et al 2012). M. peregrina is distributed in tropical and non-tropical areas.…”
Section: Introductionmentioning
confidence: 99%
“…M. peregrina is distributed in tropical and non-tropical areas. Egypt, Ethiopia to Somalia, Sudan, the Red Sea region, Palestine and Jordan are the main centers of distribution (Lalas et al 2012). It has been shown that M. peregrina has high aridity adaptation with short germination time after irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…This report agreed with the present work in which, water extract of M. stenopetala seeds was equivalent in effectiveness to crude 80% methanol extract of the seeds against S. aureus with MIC value of 1.25mg/ml and it is also equivalent in effectiveness with crude 80% methanol extract of the seeds and ethyl acetate extract of root barks against E. coli, ethyl acetate extract of stem barks against S. aureus and chloroform extract of root barks against S. boydii at MIC value of 10mg/ml. Lalas et al (2012) analyzed antibacterial activity of nhexane extract of Moringa peregrina seeds with MIC value of 4.5mg/ml against S. aureus. Busani et al (2012) also reported that, acetone extract of M. oleifera leaves inhibited the growth of S. aureus at MIC value of 5mg/ml.…”
Section: Minimum Inhibitory Concentration Of Crude Extractsmentioning
confidence: 99%
“…Antimicrobial activities of M. peregrine oil extracted from seeds were fully studied. The oil had inhibitory effects on Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, Escherichia coli, Enterobacter cloacae, Klebsiella pneumoniae, Candida albicans, C. tropicalis and C. glabrata (Lalas et al, 2002). The chemical properties of M. peregrina were studied by El-Batran et al (2005).…”
Section: Introductionmentioning
confidence: 98%